2023
DOI: 10.5194/se-14-1031-2023
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and elemental geochemical characteristics of Taodonggou Group mudstone in the Taibei Sag, Turpan–Hami Basin: implication for its formation mechanism

Huan Miao,
Jianying Guo,
Yanbin Wang
et al.

Abstract: Abstract. Organic matter types in the Taodonggou Group mudstone exhibit significant differences with depth. In order to understand the formation mechanism of this special phenomenon, we analyzed the mineralogy and geochemistry of the mudstone, as well as the source rocks, depositional environment, and depositional processes of the Taodonggou Group. Based on this, we have gained the following insights. (1) The Taodonggou Group mudstone was deposited in an intermediate-depth or deep, dysoxic, freshwater–brackish… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…can be used as a basis for judging redox conditions. In combination with the criteria for determining redox conditions, , the depositional environments of different types of effective seepage channels can be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…can be used as a basis for judging redox conditions. In combination with the criteria for determining redox conditions, , the depositional environments of different types of effective seepage channels can be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the mineral composition of shale plays a crucial role in determining the reservoir alteration difficulty, often represented by the brittleness index. This index is determined by the proportion of brittle minerals in the shale [48]. The brittleness index of Longmaxi Formation shale in the study area ranges from 21.23 to 72.7, with an average value of 44.53.…”
Section: Mineralogymentioning
confidence: 99%
“…In addition, scholars have investigated the effect of the widely distributed bedding structure in shale on hydraulic fracture propagation, pointing out that the bedding structure is the key to the generation of a complex network of seams by hydraulic fractures (Tan et al 2018;Suo et al 2020). Besides discontinuities, researchers have also investigated the effects of shale mineral composition and connections between mineral grains on hydraulic fracture propagation behaviors, pointing out that mineral composition indirectly affects hydraulic fracture propagation paths by influencing shale characteristics such as inhomogeneity, anisotropy, mechanical properties, and pore structure (Bakhshi et al 2020;Chen 2022a;Li et al 2020;Miao et al 2021Miao et al , 2023Sun et al 2021;Xiong et al 2021;Zeng et al 2019;Liang et al 2019). Then, scholars also analyzed the stress state of the subsurface shale and found that the length of hydraulic main cracks becomes larger with the increase of the main stress difference (Blanton 1982(Blanton , 1986Renshaw and Pollard 1995;Gu and Weng 2010;Gu et al 2012).…”
Section: Introductionmentioning
confidence: 99%